2017
DOI: 10.1111/fcp.12267
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine, an L‐type calcium channel blocker, protects against chlorpromazine‐induced neurobehavioural deficits in mice

Abstract: This study investigated the modulatory and chemopreventive benefit of amlodipine (AML), a dihydropyridine calcium channel antagonist, against neurobehavioural abnormalities (NAs) associated with chlorpromazine (CPZ) toxicity in mice. Adult mice were divided into five groups of six animals/group. Group 1 (control) was administered saline (10 mL/kg i.p.). Group 2 received CPZ (2 mg/kg i.p.). Groups 3 and 4 received bromocriptine (BMC, 2.5 mg/kg s.c.) and AML (1 mg/kg s.c.), respectively, while group 5 received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition to stabilizing cellular and mitochondrial Ca 2+ homeostasis, azelnidipine protects renal cells from apoptosis induced by hypoxic injury through inhibition of the MPT, cytochrome c release, and downstream signaling cascades. Amlodipine is also an L-type calcium antagonist 25 . Therefore, we hypothesized that AC would inhibit intracellular calcium influx and reduce Ca 2+ accumulation in both the cellular cytoplasm and mitochondria of NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stabilizing cellular and mitochondrial Ca 2+ homeostasis, azelnidipine protects renal cells from apoptosis induced by hypoxic injury through inhibition of the MPT, cytochrome c release, and downstream signaling cascades. Amlodipine is also an L-type calcium antagonist 25 . Therefore, we hypothesized that AC would inhibit intracellular calcium influx and reduce Ca 2+ accumulation in both the cellular cytoplasm and mitochondria of NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…L‐type calcium channel (LTCC) blockers play an important role in hypertension, angina, and heart failure. In recent studies, we found LTCC blockers also have positive effects on protecting against chlorpromazine‐induced neurobehavioral deficits and ameliorating anxiety and fear response of post‐traumatic stress disorder (PTSD) . However, from Chouabe.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 types associated with the cardiovascular system are the L-type (long-lasting), found in skeletal and smooth muscle cells, and the T-type (transient), which are found in any cell that has pacemaker activity. 3 Amlodipine targets the L-type receptor leading to reduced electromechanical conduction resulting in bradycardia, reduced contractility, vasodilation, and hemodynamic collapse. 4 First-line management of CCB poisoning includes fluid administration, intravenous calcium, vasoactive medications, and high-dose insulin.…”
Section: Introductionmentioning
confidence: 99%